2018
DOI: 10.1093/bioinformatics/bty355
|View full text |Cite
|
Sign up to set email alerts
|

Efficient flexible backbone protein–protein docking for challenging targets

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
150
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 54 publications
0
150
0
Order By: Relevance
“…We modeled backbone flexibility by incorporating a pre-generated ensemble of backbone conformations during docking. With RosettaDock 4.0, 8 we sampled over fifty conformations for each partner to successfully model T122. Despite having an efficient backbone sampling algorithm, we failed to model T131 and T132 due to the absence of conformations where the interacting loops were in near-bound conformation.…”
Section: Discussionmentioning
confidence: 99%
“…We modeled backbone flexibility by incorporating a pre-generated ensemble of backbone conformations during docking. With RosettaDock 4.0, 8 we sampled over fifty conformations for each partner to successfully model T122. Despite having an efficient backbone sampling algorithm, we failed to model T131 and T132 due to the absence of conformations where the interacting loops were in near-bound conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these efforts, a generalizable model selection strategy that captures high-level features such as topology, and secondary structure organization has yet to be developed. Previously reported methods have shown that recurring structural features (motifs) can be used to accelerate conformational searches and assist in structure evaluation (30,41,42). We have developed a novel approach that uses a CNN to capture and quantify such features.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially notable because transmembrane membrane helices are notorious for kinks and curvature (50). Programs for incorporating backbone flexibility have emerged for soluble proteins (51,52) and these developments will soon translate to membrane proteins. Another challenge is incorporating the effect of bilayer deformations induced by the protein that influence the landscape of available protein-protein complex conformations (53).…”
Section: Challenges For Modeling Of Protein-protein Interactions In Tmentioning
confidence: 99%